Prasugrel Inappropriate Use in Patients Post-percutaneous coronary intervention (PCI). A Single Center Study - Ahmed Amro; Kanaan Mansoor; Mohammad Amro; Amal Sobeih; Obadah Aqtash; Hisham Hirzallah; Alaa Gabi; Madhulika Urella; Waseem Ahmed; Sandra Shenouda; Rameez Sayyed (Marshall Journal of Medicine, 2019)
Prasugrel is a thienopyridine that was approved by the US Food and Drug Administration (FDA) in combination with aspirin for the reduction of thrombotic events as well as stent thrombosis in patients with ACS who undergo PCI. This retrospective study aims to assess the frequency of inappropriate use of prasugrel and to emphasize that prasugrel still needs more attention as inappropriate use may result in significant morbidity.